Assessment of the Chinese driver licensing system implemented from 1 Jan 2013 to 30 Sep 2016. (June 2017) - Suo, Qinghui; Zhang, Daming; Liu, Yang
Abstract: Under the conditions of the driver licensing system implemented from 1 Jan 2013 to 30 Sep 2016, learners gradually obtained their full driving privileges in China, and the Chinese driver licensing system is largely a type of Graduated Driver Licensing system. Comparative analyses were applied to identify the deficiencies of the driver licensing system (Edition of 2013). The Chinese driver licensing system primarily focuses on driver education/training, which is conducted in commercial driving schools. The learner stage is actually the driver training stage, and the length of the learner stage is not sufficient; i.e., supervised driving cannot be guaranteed, which is controversial with the principle of the GDL system. Learners' driving skills are primarily obtained by mass practice, which cannot be retained well; besides, many novice drivers do not own a car and live with parents who are experienced drivers in China and therefore seldom practice driving during the probationary period. Certain important restrictions to intermediate-stage driving – such as night driving, which has been demonstrated to be effective in reducing road accidents – are not applied. The investigations of novice drivers were also conducted to assess the system, and the results indicate that most driving leaners prepared for their driving knowledge test by mass practice, and the updated driving knowledge tests indicate that their driving knowledge faded over time. Only 66.9% of the participants passed the simulated test 3–5 months after being licensed. Investigations on in-vehicle training indicate that the average actual training time is shorter than the minimum legal requirement, although the research populations successfully passed the tests. In general, the driver licensing system of the 2013 edition cannot achieve its intended results based on the work presented in this paper. This work can be used as a reference for the driver licensing system reform in the future.